2002
DOI: 10.1046/j.1439-0264.2002.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Observations on the Platelets of the Arabian Tahr (Hemitragus jayakari)

Abstract: The ultrastructure of platelets was studied in specimens of peripheral blood from 18 healthy adult Arabian tahrs (Hemitragus jayakari). The platelets were characterized by their extreme polymorphism. The number of alpha granules, typically one to six per cell, was considerably less than that reported for most animal platelets. Similar to humans, the platelets of the Arabian tahr had nucleoids within the alpha granules. However, nucleoids were not a consistent finding. One or more electron-dense granules, most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Typically, most platelets of the Arabian oryx, exhibited between 1–2 electron‐dense bodies (Figure ), similar to the number found in the Arabia tahr (Johnson et al, ) but unlike those in humans and camels with 5–7 electron‐dense bodies per cell (Gader et al, ) Electron‐dense bodies have also been reported in other wild and domestic animal species including the white and black rhinoceros (Du Plessis et al, ) and buffalo (Du Plessis et al, ). They are characterized as being clear vesicles with an electron‐dense core.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…Typically, most platelets of the Arabian oryx, exhibited between 1–2 electron‐dense bodies (Figure ), similar to the number found in the Arabia tahr (Johnson et al, ) but unlike those in humans and camels with 5–7 electron‐dense bodies per cell (Gader et al, ) Electron‐dense bodies have also been reported in other wild and domestic animal species including the white and black rhinoceros (Du Plessis et al, ) and buffalo (Du Plessis et al, ). They are characterized as being clear vesicles with an electron‐dense core.…”
Section: Resultssupporting
confidence: 65%
“…Alpha granules are commonly found in the platelets of many animal species. In the Arabian oryx (Figure ), they exhibited a variety of shapes and sizes, as described for the Arabian tahr (Johnson et al, ). The α granules of humans are more homogenous in shape and size (Sharda & Flaumenhaft, ) and those from buffalo are characteristically described as large (Du Plessis et al, ).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations